Ikonostas - Misijuk, Tatiana (Elpis, 2014)
The paper indicates a complex meaning of the iconostasis both in sacred art and liturgics of the Orthodox Church. Selected examples illustrate a process of historical development of the iconostasis, contemporary variety of forms and its influence on worship celebrated in the Orthodox church.